Pendampingan Pembelajaran Matematika Berbantuan GeoGebra pada Materi Geometri tingkat SMA di Pesisir Selatan - Meria Gusteti; Khairul Azmi; Suci Wulandari; Widya Rahmalina; Asrina Mulyati; Ria Finolia; Fitri Miftahurrizky; Haura Qhonitah (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
This community service program aimed to implement GeoGebra as a systemic innovation in geometry learning at MAN 2 Pesisir Selatan. The program was designed to address students' visual abstraction barriers and strengthen teachers' pedagogical capacity through interactive mentoring and the utilization of open-source technology. Evaluation was conducted comprehensively using a 10-item student response questionnaire. Descriptive analysis results showed an overall mean score of 3.32, categorized as